Correlation of antioxidant and radical scavenging activity in Hydrangea macrophylla L. extract from various cultivars - CHOI, Yoo-Min; JEON, So-Heon; HER, Mi-ra; YIM, Soon-Ho (Food Science and Technology, 2023)
In this study, the polyphenol content [total polyphenol content (TPC), total flavonoid content (TFC), and total anthocyanin content (TAC)] and antioxidant activity [1,1-diphenyl-2-picrylhydrazyl (DPPH), 2,2'-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS), ferric ion reducing antioxidant power (FRAP), phosphomolybdenum complex assay (PMA), and oxygen radical absorbance capacity (ORAC)] of hydrangea leaf extract, collected based on the cultivation method of each variety, were confirmed, and the correlation between them was evaluated. To confirm the polyphenol content, TPC, TFC, and TAC contents were measured. The TPC was highest in Morning Star (open field) at 4.65 ± 0.00 mg tannic acid equivalent/g, while the TFC was highest in Hydrangea serrata (open field) at 6.44 ± 0.00 mg catechin equivalent/g. The anthocyanin content was highest in H. serrata (open field) at 1.56 ± 0.00 mg CGE/100 g DW. The antioxidant activity (PMA and FRAP) using the reducing power of transition metal ions was 6.17 ± 0.00 mg ascorbic acid equivalent/g in H. serrata (greenhouse) and 140.76 ± 0.00 mM Trolox equivalent (TE)/g in H. serrata (open field). The antioxidant activities measured by radical scavenging assays were highest in White ari (open field) for ABTS at 9.97 ± 0.00 mM TE/g, H. serrata (open field) for DPPH at 28.48 ± 0.00 mM TE/g, and H. serrata (open field) for ORAC at 81.09 ± 0.31 mM TE/g. Our study established a significant quadruple correlation between TPC and radical scavenging activity (ABTS, DPPH, and ORAC) and between transition metal ion (FRAP) and radical scavenging activity (ABTS, DPPH, and ORAC).